Photobiomodulation Therapy in the Management of Oral Lichen Planus: A Systematic Review and Meta-Analysis - Soh, Wei Kang; Cheah, Kwok Fu; Veettil, Sajesh K.; Pandiar, Deepak; Nimbalkar, Smita; Gopinath, Divya (European Journal of Dentistry, 2024)
Photobiomodulation therapy (PBMT) is a non-invasive and the latest form of therapy used in the treatment of non oncological diseases as well as cancers of various types and locations. The aim of this study was to systematically review and assess the efficacy of PBMT in managing oral lichen planus (OLP) compared to the interventions. A systematic review and meta-analysis were implemented according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. An electronic search using PubMed, Scopus, and Cochrane was conducted to retrieve relevant studies published until June 2023. The outcomes evaluated included the reduction in pain score and clinical severity scores (Prospero No CRD42023428626). A total of eight studies were identified for qualitative synthesis. The pooled analysis incorporating six studies revealed that there are no significant differences for both mean pain score (mean difference [MD] = 0.21, 95% confidence interval [CI] = −0.51, 0.93) as well as clinical score (MD = −0.08, 95% CI = −0.4, 0.25) between PBMT and comparison groups. Subgroup analysis based on corticosteroids as controls showed that there was no significant difference in mean reduction in pain score between PBMT and topical steroids (MD = 0.38, 95% CI = −0.54, 1.31). PBMT is as effective as other interventions in the treatment of OLP, though not superior, and can be a promising alternative treatment for cases resistant to steroids or when steroids are contraindicated. Further studies are recommended to standardize the optimal settings for the treatment of OLP.
Keywords: photobiomodulation therapy; oral potentially malignant disorder; lichen planus; OLP; low-level laser therapy